Type Ia supernovae from exploding oxygen-neon white dwarfs - Marquardt, Kai S.; Sim, Stuart A.; Ruiter, Ashley J.; Seitenzahl, Ivo R.; Ohlmann, Sebastian T.; Kromer, Markus; Pakmor, Rüdiger; Röpke, Friedrich (Astronomy and astrophysics, 2015)
Context. The progenitor problem of Type Ia supernovae (SNe Ia) is still unsolved. Most of these events are thought to be explosions of carbon-oxygen (CO) white dwarfs (WDs), but for many of the explosion scenarios, particularly those involving the externally triggered detonation of a sub-Chandrasekhar mass WD (sub-MCh WD), there is also a possibility of having an oxygen-neon (ONe) WD as progenitor. Aims. We simulate detonations of ONe WDs and calculate synthetic observables from these models. The results are compared with detonations in CO WDs of similar mass and observational data of SNe Ia. Methods. We perform hydrodynamic explosion simulations of detonations in initially hydrostatic ONe WDs for a range of masses below the Chandrasekhar mass (MCh), followed by detailed nucleosynthetic postprocessing with a 384-isotope nuclear reaction network. The results are used to calculate synthetic spectra and light curves, which are then compared with observations of SNe Ia. We also perform binary evolution calculations to determine the number of SNe Ia involving ONe WDs relative to the number of other promising progenitor channels. Results. The ejecta structures of our simulated detonations in sub-MCh ONe WDs are similar to those from CO WDs. There are, however, small systematic deviations in the mass fractions and the ejecta velocities. These lead to spectral features that are systematically less blueshifted. Nevertheless, the synthetic observables of our ONe WD explosions are similar to those obtained from CO models. Conclusions. Our binary evolution calculations show that a significant fraction (3-10%) of potential progenitor systems should contain an ONe WD. The comparison of our ONe models with our CO models of comparable mass (~1.2 M⊙) shows that the less blueshifted spectral features fit the observations better, although they are too bright for normal SNe Ia.